Contribution to the knowledge of mycobiota of the San Sebastián del Oeste region, Jalisco, Mexico - Herrera Fonseca, María de Jesús; Guzmán-Dávalos, Laura; Rodríguez, Olivia (Instituto de Ecología, A.C., 2005)
A preliminary inventory of fungi, most of them macrofungi, from the municipality of San Sebastián del Oeste, Jalisco, Mexico, studied in three years, is presented. The area is largely characterized by pine, oak, mesophytic, tropical deciduous and tropical subdeciduous forests with few agriculture zones. Based on 583 specimens, 216 species were identified, of which 89.4% correspond to Basidiomycota, 8.8% to Ascomycota, 1.3% to Myxomycota and 0.5% to Deuteromycota. Furthermore 35 new records for the state of Jalisco and two new species for Mexico: Amanita roseitincta (Murrill) Murrill and Ramaria abietina (Pers. : Fr.), are documented.